Pengaruh Aktivitas Fisik Terstruktur Terhadap Peningkatan Persentase Massa Otot Pada Anggota Sanggar Senam - Farah Zahida; Fatimah Eliana Taufik; Diniwati Muchtar (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2018)
Health is very important in life. They are many ways for life healthy such as by doing structured physical activity. Physical activity has positive effect to prevent the decrement of muscle mass. Muscle mass is important for energy, performance and metabolism regulation. Therefore, the purpose of this study is to find out the effect of the structured physical activity with the increment of muscle mass percentage on member of gymnastics studio This study is used the one group pretest postest design. The population and the sample are the member of R and K gymnastic studio in Cempaka Putih and Johar Baru with 36 people. The samples are chosen by purposive sampling. The data are collected by measuring the respondent's body with Bioelectrical Impedance Analysis on the begining and the ending of this study. The data is analyzed with t-test used Wilcoxon method. Fourteen respondents (56%) from twenty-five have their muscle mass percentage increased with the p value 0,253. There are no significant effect within the strucured physical activity and the increase of muscle mass percentage on member of gymnastics studio.